Fixed and mobile PM2.5, CO, and CO2 measurement campaigns in light, dense, and heavy metropolitan vehicular traffic with a low-cost portable air pollution sensing device - Chen, Sidney C. (Animo Repository, 2019)
Using a low-cost portable air pollution measurement device with positioning, and a monitoring station user interface via web application developed by the authors, stationary and in-motion measurements of particulate matter 2.5 (PM2.5), carbon monoxide (CO), and carbon dioxide (CO2) are reported. The measurement of the air pollutants was done along roads and roadsides in Metro Manila, Philippines at light, medium, and heavy vehicular traffic conditions. The outcomes show that the device and systems work well and can be used as a reference for air pollution data. © 2019, World Academy of Research in Science and Engineering. All rights reserved.